HOW IS PRINCIPAL LEADERSHIP RELATED TO EFFECTIVE SCHOOL? - Arjanto, Paul (Faculty of Education Universitas Negeri Malang, 2022)
This article examines the leadership of school principals to create effective schools. This study is in the form of a literature review to understand how principals create effective schools and their impact on improving the quality of schools in general. Researchers conducted an analysis of 20 articles published in the period 2010-2022. All articles are written in Indonesian. The results showed that research on the topic of principals' leadership has implications for the creation of effective schools. This finding specifically highlights the creation of effective schools in three ways, namely 1) principal leadership characteristics, 2) principal leadership strategies, and 3) principal leadership style.